Dairy Supply Chain Risk Management in Bangladesh: Field studies of Factors and Variables - Tasnuba Nasir; Mohammed Quaddus; Mohamamd Shamsuddoha (Institute of Research and Community Outreach - Petra Christian University, 2014)
Supply chain risk management (SCRM) has gained wide attention among the academia and the business community in the present competitive business world. This paper aims to investigate the main risk factors associated with the dairy industry along with focuses on possible mitigation strategy to mitigate those risks. Qualitative field study has been undertaken in this research. The results of the interviews identify the different risk issues along with the possible mitigation strategies, embedded at storage, processing and distribution level in dairy industry of Bangladesh. The practical implication will contribute significantly to the dairy sector in terms of mitigating risks.